PENGARUH LUMPUR SAWIT FERMENTASI DENGAN SUPLEMENTASI ASAM AMINO LISIN, METIONIN, TRIPTOPAN SELAMA PRODUKSI TERHADAP PERFORMANS DAN KUALITAS INTERNAL SERTA KADAR KOLESTEROL TELUR AYAM RAS - Yosi Fenita; Desia Kaharuddin (Jurnal Agroindustri, 2011)
The  aim of this study was  to evaluate the effect of feeding fermented   palm oil sluge and critical amino acid (CAA) ; methyonine, lysine, and tryptophan supplementation on diet to performance, egg internal quality and egg cholesterol level. The research design used was  complety randomized design with 4 teatments  with 80 layer;  each treatment consists of  P0 ; the control diet, without addition of critical amino acid.  P1 ; the diet contains of 50% critical amino acid (P1:50% (Lys 404.5 mg/kg ; Met 250 g/kg ; Trp 90,5 gr), P2: suplementasi 75% (Lys 606,75 mg/kg; Met 375,75 mg/kg; Trp 137,75 mg/kg), P3: suplementasi 100% (Lys 809 mg/kg; Met 501 mg/kg; Trp 90.5mg/kg) on diet.. Variable 0bserved were feed comsumption, feed conversi, egg weight, egg production, yolk colour, yolk index, albumen index, shell thickness, air cell and egg cholesterol level  that feeding 100% supplementation consisting of (Lys 809 mg/kg; Met 501 mg/kg; Trp 90.5 mg/kg) significantly (P<0.05).  In conclutions, P3 (Lys 809 mg/kg; Met 501 mg/kg; Trp 90.5 mg/kg)  teatment group was significant on yolk colour, yolk index, albumen index, air cell and cholesterol level.